Dysglycemia in Children with Severe Acute Malnutrition: A Systematic Review and Meta-Analysis. Issue 3 (11th November 2020) - Ledger, Elizabeth; Harawa, Philliness Prisca; Daniel, Allison I; Candler, Toby; Prentice, Andrew M; Bandsma, Robert H J
ABSTRACT: Dysglycemia is a common complication of severe acute malnutrition (SAM) in children. Its prevalence and impact on short- and long-term outcomes are not well described. This systematic review was undertaken to review the available evidence on dysglycemia (either hypo- or hyperglycemia) in hospitalized children with SAM. The 2 primary objectives of this systematic review were to understand the prevalence of hypoglycemia and hyperglycemia in children with SAM. A secondary objective was to understand the relation between dysglycemia and clinical outcomes like mortality in children with SAM. MEDLINE was searched with terms related to children, SAM, and dysglycemia. A meta-analysis of proportions was completed to determine the hypoglycemia prevalence and a standard meta-analysis was done to determine the relation between hypoglycemia and mortality. The certainty of the evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. A total of 2148 articles were identified in the database search of which 16 met the inclusion criteria for the systematic review based on screening done by multiple reviewers. The overall prevalence of hypoglycemia in SAM across studies based on the meta-analysis of proportions was 9% (95% CI: 7%, 12%; I 2  = 92%). Meta-analysis results showed that hypoglycemia was associated with a higher chance of mortality during hospitalization in children with SAM (OR: 4.29; 95% CI: 3.04, 6.05; I 2  = 0%). According to the GRADE evaluation, the certainty of the evidence for the prevalence of hypoglycemia was low and for hyperglycemia was very low. For the relation between hypoglycemia and mortality, the certainty of the evidence was moderate. A meta-analysis was not carried out for the prevalence of hyperglycemia due to the wide range of definitions used for across studies, but the prevalence ranged from 2% to 38% in the literature. This systematic review highlights the need for further work in this area to include serial glucose measurements to understand the clinical importance of dysglycemia during hospitalization in children with SAM.